IMPROVING WRITING SKILL THROUGH THINK-PAIR-SHARE ON DESCRIPTIVE TEXT IN THE SECOND GRADERS OF MTs. NURUL ISLAM SLATRI , BREBES - Muhammad Arifudin Aziz (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2021)
Writing is assumed as the most difficult skill among other skills. Meanwhile, explaining all the materials until the end of the class is still used in the teaching process of descriptive text. This research is generally to answer whether or not think-pair-share can improve students’ writing skill on descriptive text and specifically to know: (1) the teacher’s activities, (2) the students’ activities, and (3) the students’ responses during the implementation of think-pair-share on writing class of descriptive text. The subjects are 16 students of the second graders of MTs Nurul Islam Slatri in the academic year of 2013/2014. The data were obtained from the observations and writing test. The students’ writing skill improved after the implementation of Think-Pair-Share that could be seen in the improvement of mean score, from 68.4 and 72.5 in cycle one to 73.4 and 77.2 in cycle two. The percentage of students who passed the minimum mastery criteria also improved, from 62.5 % and 69 % in cycle one to 75 % and 100 % in cycle two. In conclusion, think-pair-share can improve students’ writing skill on descriptive text.